2020
DOI: 10.1161/circinterventions.120.009565
|View full text |Cite
|
Sign up to set email alerts
|

One-Month Dual Antiplatelet Therapy Following Percutaneous Coronary Intervention With Zotarolimus-Eluting Stents in High-Bleeding-Risk Patients

Abstract: Background: Despite treatment guidance endorsing shortened dual antiplatelet therapy (DAPT) duration in high bleeding risk (HBR) patients after drug-eluting stents, limited evidence exists to support these recommendations. The present study was designed to examine the safety and effectiveness of 1-month DAPT duration following percutaneous coronary intervention with zotarolimus-eluting stents in HBR patients. Methods: Onyx ONE Clear was a prospective, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…24 In addition, it showed no between-stent difference in the risk of ST. Another analysis that included 1,506 HBR patients, who did not have any major adverse events during the first month, confirmed the safety and efficacy of the RO-ZES following 1 month of DAPT by meeting the prespecified performance goal. 25 In the O-SES group of our study, the 3-year rate of definite-or-probable ST (1.2%) was in line with that of other all-comer trials. 18,26 Looking at all the available evidence, the RO-ZES appears to be associated with a particularly low risk of ST.…”
Section: Discussionsupporting
confidence: 90%
“…24 In addition, it showed no between-stent difference in the risk of ST. Another analysis that included 1,506 HBR patients, who did not have any major adverse events during the first month, confirmed the safety and efficacy of the RO-ZES following 1 month of DAPT by meeting the prespecified performance goal. 25 In the O-SES group of our study, the 3-year rate of definite-or-probable ST (1.2%) was in line with that of other all-comer trials. 18,26 Looking at all the available evidence, the RO-ZES appears to be associated with a particularly low risk of ST.…”
Section: Discussionsupporting
confidence: 90%
“…Due to high rate of radial access in our study, vascular access strategies were minimally associated with these observed reductions in bleeding rates over time. The use of new-generation DES featuring much lower strut thickness and biodegradable polymers or polymer- free designs allows the shortening of DAPT ( 18 20 ). Also, use of intravascular imaging to optimize the PCI procedure and achieve more complete endothelialization is important in patients at high risk of bleeding who might need a short duration of DAPT ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…20 Finally, there is increasing evidence that with a number of third generation DESs 1 month of DAPT can safely be used in patients at high bleeding risk without an increase in ischaemic events. [21][22][23] A single antiplatelet agent is continued in all cases after discontinuation of DAPT, this tends to be aspirin. In some cases, for example, patients who had a previous stroke, the patients may have aspirin stopped at the end of the DAPT course and clopidogrel continued long-term.…”
Section: P2y12 Receptor Antagonistsmentioning
confidence: 99%